Review Article : Skrining Fitokimia Ekstrak Daun Jambu Biji (Psidii Guajava L.) Sebagai Kosmetika - Prasetya, Fajar Adi; Fikayuniar, Lia; Nurshazidah, Shania; Wijaya, Gina Desfina; Atoriq, Muhamad Al (Jurnal Ilmiah Wahana Pendidikan, 2024)
The beauty and health of a person's facial skin will be disturbed if there are abnormalities in the facial skin, because the face is very important and vital for women. One of the disorders on facial skin that often occurs is the appearance of acne. The aim of this research is to carry out phytochemical screening using many methods on Guava Leaf simplicia (Psidii Guajava L.) which is used as an active substance in cosmetic preparations. Data was obtained from electronic databases, namely scientific articles and research journals through electronic databases such as Media Neliti, PubMed, Sinta Kemendikbud, Researchgate.Net, Google Scholar, and Science Direct. Plants that are scientifically proven to have anti-acne activity are guava leaves (Psidium guajava L.). Acetone:water extract (7:3) of guava leaves has antibacterial activity against Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis. Based on the results of the review of the article that has been carried out this time regarding Phytochemical Screening of Guava Leaf Extract (Psidii Guajava L.) as a Cosmetic, it can be concluded that Guava Leaves (Psidium guajava L.) have antibacterial activity that causes acne.